Domestic violence and decision-making power of married women in Myanmar: analysis of a nationally representative sample - Kabir, Russell; Haque, Mainul; Mohammadnezhad, Masoud; Samad, Nandeeta; Mostari, Shabnam; Jabin, Shiny; Majumder, Md Anwarul Azim; Rabbani, Md Golam (Annals of Saudi medicine, 2019)
Women in Myanmar are not considered decision makers in the community and the physical and psychological effect of violence makes them more vulnerable. There is a strong negative reaction, usually violent, to any economic activity generated by women among poorer and middle-class families in Myanmar because a woman's income is not considered necessary for basic survival. Explore the relationship between domestic violence on the decision-making power of married women in Myanmar. Cross-sectional. National, both urban and rural areas of Myanmar. Data from the Myanmar Demographic and Health Survey 2015-16 were used in this analysis. In that survey, married women aged between 15 to 49 years were selected for interview using a multistage cluster sampling technique. The dependent variables were domestic violence and the decision-making power of women. Independent variables were age of the respondents, educational level, place of residence, employment status, number of children younger than 5 years of age and wealth index. Domestic violence and decision-making power of women. 7870 currently married women. About 50% respondents were 35 to 49 years of age and the mean (SD) age was 35 (8.4) years. Women's place of residence and employment status had a significant impact on decision-making power whereas age group and decision-making power of women had a relationship with domestic violence. Giving women decision making power will be indispensable for the achievement of sustainable development goals. Government and other stakeholders should emphasize this to eliminate violence against women. Use of secondary data analysis of cross-sectional study design and cross-sectional studies are not suitable design to assess this causality. Secondly the self-reported data on violence may be subject to recall bias. None.